Prospective devices to prevent unauthorized lowering of vehicle platform (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article reveals promising devices to prevent the vehicle's platform from lowering the vehicle. The theoretical study obtained the results of the study of the operation of agricultural transport equipment with a hydraulic drive of the discharge device. Also the results of the analysis of serial technical solutions of safety and blocking systems of the platform of agricultural transport equipment. Precautionary and blocking systems for agricultural transport vehicles were developed in the form of four patents. Designed safety and blocking systems for the safety of the operation of agricultural transport equipment, which provide the fixation of the platform in the refusal of the hydraulic drive of the discharge device.
Keywords: vehicle; platform; operation; hydraulic cylinder